2012
DOI: 10.1080/20786204.2012.10874177
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and alcohol use among healthcare workers in three public hospitals in KwaZulu-Natal, South Africa

Abstract: In South Africa, the smoking prevalence among adults has declined from 34% (52% male and 17% female) in 1995 4 to 21.4% (35.8% male and 8.1% female) in 2003. 5 The smoking prevalence among health care workers (HCWs) varies widely around the world. A study carried out in 1991 among hospital staff at Llandough Hospital, Cardiff, showed that 20% of nurses and 5% of doctors smoked. 6 A review by Smith and Leggat carried out in 2004 showed a high smoking prevalence among physicians in Greece (49%), China (45%), Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…It is however higher than the prevalence reported among nurses in Norway, 0.3% (Edvardsen et al, 2014). The prevalence in this study is comparable to the reported prevalence (22%) among healthcare professionals, including nurses in another province of South Africa (Okeke, Ross, Esterhuizen, & Van Wyk, 2012). Also, it is comparable to the reported prevalence among doctors in Nigeria, 30.3% (Obadeji, Oluwole, Dada, Adegoke, 2015).…”
Section: Lack Of Initiativesupporting
confidence: 72%
“…It is however higher than the prevalence reported among nurses in Norway, 0.3% (Edvardsen et al, 2014). The prevalence in this study is comparable to the reported prevalence (22%) among healthcare professionals, including nurses in another province of South Africa (Okeke, Ross, Esterhuizen, & Van Wyk, 2012). Also, it is comparable to the reported prevalence among doctors in Nigeria, 30.3% (Obadeji, Oluwole, Dada, Adegoke, 2015).…”
Section: Lack Of Initiativesupporting
confidence: 72%
“…However, behavioural intervention remains an underexploited segment of tobacco control in SA. [15,16] Evidence shows scant and inconsistent availability of smoking cessation behavioural support in primary care facilities. [6,10] According to the WHO, behavioural intervention was not consistently offered in public hospitals or health clinics in SA as of December 2016, and the government does not cover the cost of such support.…”
Section: Smoking Cessation In South Africa and Beyondmentioning
confidence: 99%
“…[9] Evidence shows that combining expert behavioural support with pharmacotherapy is the most effective cessation strategy. [9,16] Compared with unaided smoking cessation attempts, NRT makes it one-and-a-half times more likely for a person to succeed, while varenicline and bupropion double the chance of success in quitting attempts. [16] On the other hand, combining pharmacotherapy with expert support makes someone up to four times as likely to stop smoking successfully.…”
Section: Smoking Cessation In South Africa and Beyondmentioning
confidence: 99%
See 2 more Smart Citations